Unexpectedly long survivorship on seawater of multiple coastal beetles indicates the possibility of "floating dispersal" for transoceanic migration. Issue 3 (12th June 2020) - Ueno, Hiroto; Kitagawa, Kosaku; Matsubayashi, Kei W.
Abstract: Ocean is generally a major barrier of migration for most flightless land animals; however, terrestrial flightless insects often demonstrate wide range distribution across oceans. To elucidate the mechanism of flightless insects to expand their distribution over the sea, we measured the survivorship of nine species of coastal beetles on seawater (i.e. seawater tolerance). We observed that two out of nine coastal beetle species showed over 10 days of median survival days (50% death days), and nearly 1 month of maximum survival days. From the unexpectedly long survival on the surface of seawater, we propose the hypothesis of "floating dispersal, " where individuals simply float on the sea surface and cross the ocean with currents. This mode can provide a novel explanation of transoceanic migration/distribution of flightless animals. Abstract : Measurement of seawater tolerance of nine coastal flightless beetle species including (a) Phelopatrum scaphoides . (b) Scepticus tigrinus showed that some of them exhibit unexpectedly long survival days on seawater. From the results, we propose 'floating dispersal' as the novel mode for transoceanic migration of flightless animals.